There is no inclusive fitness at the level of the individual. (December 2016) - Allen, Benjamin; Nowak, Martin A
Abstract : Highlights: We report two points of mathematical agreement between critics and supporters of inclusive fitness theory. First, in general, inclusive fitness does not exist at the level of the individual. Second, in general, natural selection does not lead to inclusive fitness maximizing behavior. Abstract : Inclusive fitness theory attempts to explain the evolution of social behavior at the level of the individual. The inclusive fitness of an individual is defined as the sum of all the effects this individual has on itself and others, with each term multiplied by a relatedness coefficient. However, this quantity does not exist for most evolutionary processes, because biological interactions are typically nonlinear and fitness effects are not additive. Six recent publications, by proponents of inclusive fitness theory and outside observers, agree with our criticism on two mathematical points: in general, there is no inclusive fitness at the level of the individual and natural selection does not lead organisms to maximize inclusive fitness. Here we review the current state of the controversy over inclusive fitness, highlight points of mathematical agreement, and discuss prospects for a way forward.